Effect of carboxymethyl cellulose on properties of wheat flour-tapioca starch-based batter and fried, battered chicken product - Pongsawatmanit, Rungnaphar; Ketjarut, Soraya; Choosuk, Panusorn; Hanucharoenkul, Pattharasuda (Agriculture and Natural Resources, 2018)
Hydrocolloid is widely used to improve the quality of food. In this study, the effect of carboxymethyl cellulose (CMC) on the properties of batter and fried, battered product prepared from wheat flour (WF)-tapioca starch (TS) blends was investigated. The dry-mixes were prepared from the flour blends of 91.4% flour blend [WF/TS (1:1) and CMC (0%, 0.25%, 0.5%, 0.75% or 1.0%)], 5.5% salt and 3.1% leavening agent and then mixed with water (1:1.3) for batter preparation. The batters had a significant increase in consistency coefficient, yield stress and batter pickup with increasing CMC replacement in the dry mix. However, CMC did not significantly (p > 0.05) alter either the differential scanning calorimetry thermal properties of the batters or the rapid visco-analyzer viscosity after holding at 95 °C for 4 min. The substitution of CMC decreased the oil content but increased the moisture content in the pre-fried chickenwing sticks. After final frying at 180 °C, the oil content of the fried product was significantly (p < 0.05) reduced in the samples containing CMC (equal to or more than 0.5% in dry-mix). There were no significant (p > 0.05) differences in the overall liking scores in the fried products without and with 0.5% CMC replacement in the flour blend. The results indicated that CMC could be used in WF/TS batter preparation, enhancing the batter pickup and quality and especially acting as an oil barrier-forming ingredient for fried, battered foods.